Pengaruh Pembelajaran diluar Kelas (Outdoor Study) Terhadap Hasil Belajar IPA Siswa Kelas IV A SDN Paccinongan Unggulan - Ashar Ashar; Muliana Muliana; Roslynrosdiah Roslynrosdiah (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to determine outdoor study on student learning outcomes in Natural Sciences subjects at SDN Paccinongan Unggulan. With the research problem